(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This study explores the interplay of language anxiety, communication apprehension, and self-concept as determinants of verbal communication skills among senior secondary school students in Ibadan, Nigeria. Krashen’s Affective Filter Hypothesis and Input or Monitor Model provided the framework, while the study adopted the correlational survey design. Data were collected from 179 Senior Secondary School 2 students across four randomly selected schools. Instruments included the English Language Anxiety Scale ELCAS, Communication Apprehension Questionnaire CAQ, Verbal Communication Rating Scale VCRS, and Learners Self-Concept Questionnaire LSCQ. The findings revealed high levels of language anxiety and communication apprehension, alongside strong self-concept among participants. However, only language anxiety demonstrated a significant negative relationship with verbal communication achievement, while communication apprehension and self-concept did not significantly predict performance. These results challenge prevailing assumptions about the cumulative impact of psychological factors on language proficiency and underscore the complex nature of verbal communication challenges in this context. The study recommends interventions that lower language anxiety, improve students’ self-awareness and confidence, and blend psychological, pedagogical, and environmental strategies to reduce language anxiety, develop more accurate self-assessment tools, and further qualitative and longitudinal research to understand better the evolving dynamics of psychological factors and communication skills among Nigerian students.